Gestão social e organização comunitária no Programa Minha Casa, Minha Vida: o caso no Residencial Ruy Pereira dos Santos - Silva, Suzana Melissa de Moura Mafra da (2018)
The objective of the research is to systematize challenges and opportunities of community organization initiatives in the track 1 to PMCMV in the light of participation’s categories and social management elements. The PMCMV denotes an inflection in the trajectory of housing policies in Brazil since the last half of the 20th century. However, the predominance of agents of the construction sector in the Program has reinforced patterns of peripherization and poor location of housing complexes, which directly influence the sustainability of the Program. In consideration of sustainability, there is in the Program the prediction of social work as fomentation element to participation and social inclusion, which includes purposes of community mobilization and monitoring the daily lives of families for a given period of time. In Rio Grande do Norte, studies indicate that among the few municipalities that perform social work, the instruments that guide it have been elaborated unilaterally by municipalities and without participation of families. Advancing in this discussion, this research approaches a community organization experience in the Residencial São Gonçalo do Amarante (known as Ruy Pereira dos Santos Residential), an enterprise of the track 1 to PMCMV located in the municipality of São Gonçalo do Amarante/RN. These enterprises are segmented into 6 condominiums of 300 units each, totaling 1,800 homes with an estimated population of 7,200 people. The present dissertation, carried out in the Ruy Pereira I Condominium (CRP-I), has a qualitative nature and consists of a case study that has undergone a bibliographic review phase, for the elaboration of a theoretical reference in participation mediated by elements of social management, and, another for the systematization of academic production in the PMCMV in UFRN postgraduate programs stricto sensu. The research had also the collected primary field data through two focal group dynamics performed with CRP-I residents. The collected data were processed through the basic lexicographic analysis supported by IRAMUTEQ software. The IRAMUTEQ generated three analytical classes for the textual corpus from data collection: a) difficulties in the condominium; b) people and social relations; and c) community organization. The main findings of the research point to the Residents' Association, which must ensure community organization, can only precariously mitigate conflicts and agglutinates people. There is a strong restriction on the performance of the Association due to the high number of defaulting in the payment of the condominial fee. The recreational collective Lambe Sal, which gathers 50 men/families and assumes important community functions in the CRP-I, shows practices of social management and participation with a higher quality than that performed by the Residents' Association, which is done through voluntary work developed by own members in the cleaning and maintenance of common areas and in promoting parties on commemorative dates.